MiR-1539 and Its Potential Role as a Novel Biomarker for Colorectal Cancer - Cui, Xueyang; Lv, Zhi; Ding, Hanxi; Xing, Chengzhong; Yuan, Yuan (Frontiers in Oncology, 2021)
Purpose: The study aimed to identify the potential of miR-1539 to serve as a biomarker for predicting the risk and pathobiological behavior of CRC. Methods: The multidimensional-assay study consisted of 100 serum samples from 51 CRC cases and 49 healthy controls, and 56 paired CRC tissue samples. The relative expression levels of miR-1539 in exosomes, serum and tissue were detected and compared among different groups by reverse transcription-polymerase chain reaction (RT-PCR). Meanwhile, the diagnostic value and potential function of miR-1539 were investigated using clinicopathological data combined with bioinformatics analysis. Results: MiR-1539 was significantly upregulated in exosomes (p=0.003) and cancer tissue (p<0.001) of CRC patients. Expression levels of miR-1539 in serum varied with different tumor sites (right-sided vs. left-sided, p=0.047; left-sided CRC vs. HCs, p=0.031). Concerning diagnostic efficacy, miR-1539 in exosomes may help to distinguish CRC cases from HCs with a sensitivity of 92.2%, moreover, the specificity for left-sided CRC diagnosis could be improved to 96.6% by serum miR-1539. Combined with clinicopathological data, serum miR-1539 level was found to be positively associated with VEGF expression (p=0.028), while its level in tissue was positively associated with Ki-67 index (p=0.035). Poorer differentiation was revealed to be potentially related with an upward tendency of miR-1539 in tissue (p=0.071). Based on bioinformatics analysis, miR-1539 may have significant influence on CRC genesis and progression in terms of mechanism. Conclusion: MiR-1539 in circulation or tissue may serve as a novel potential biomarker for screening CRC and the prediction of poor clinicopathologic biological behavior.